Persepsi Mahasiswa Atas Penggunaan Aplikasi Perkuliahan Daring Saat Wabah Covid-19 - Mumuh Mulyana; Bambang Hengky Rainanto; Danti Astrini; Ratih Puspitasari (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2020)
The purpose of this study is to explore the activities and perceptions of students in conducting online lectures through applications during the COVID-19 outbreak . This research uses a quantitative approach with a survey method with the research respondents are 781 IBI Kesatuan students who are active in the Even Semester Academic Year 2019/2020. The selection of research subjects is done through purposive sampling techniques . D ata study were analyzed using analysis kuantit Atif descriptive percentage technique. The results showed that students gave positive responses to the implementation of these online lectures and were willing to always follow them. The family fully supports students to attend online lectures while at home . The limitation of internet access quota is an obstacle for students in attending online lectures. The use of GCR and WAG applications received positive responses from students because of their flexible, quota-friendly internet access and easy to use them. Keywords: online lectures, covid-19, student perceptions, applications